Eksistensi Tanah Ulayat Suku Bunggu di Provinsi Sulawesi Barat - M, Herianto; Lahae, Kahar; Arisaputra, Muhammad Ilham (Widya Yuridika, 2024)
This research aims to analyze the regulation of the use of the customary land of the Bunggu Tribe Customary Law Community in Pakawa Village, Pasangkayu Regency, West Sulawesi Province and to analyze the role of the Regional Government of Pasangkayu Regency in terms of recognizing and protecting the customary land of the Bunggu Tribe Customary Law Community. This research is an empirical type of research, the location of this research was carried out in Pakawa Village, Pasangkayu Regency, West Sulawesi Province. The results of the research show that the regulation of the use of the customary land of the Bunggu Tribe Customary Law Community in Pakawa Village, Pasangkayu Regency, West Sulawesi Province, is still being regulated using customary mechanisms, meaning that every person who owns or will manage land must have the knowledge of the traditional stakeholders. And the role of the Regional Government of Pasangkayu Regency in terms of recognizing and protecting the customary land of the Bunggu Tribe Traditional Law Community in Pakawa Village, Pasangkayu Regency, West Sulawesi Province, is only limited to recognizing the existence of the Bunggu Tribe culturally and customarily, not yet providing legal or regulatory recognition through Regional Regulations ( Regional Regulation).